2007
DOI: 10.1007/s10526-007-9142-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimal concentration of Beauveria bassiana vectored by bumble bees in relation to pest and bee mortality in greenhouse tomato and sweet pepper

Abstract: Greenhouse cage trials were conducted to determine the optimal concentration of Beauveria bassiana (Balsamo) Vuillemin (Ascomycota: Hypocreales) (BotaniGard 22WP 1 formulation) as vectored by the bumble bee, Bombus impatiens (Cresson) (Hymenoptera: Apidae) pollinator for control of greenhouse whitefly, Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae) on greenhouse tomato, tarnished plant bug, Lygus lineolaris (Palisot de Beauvois) (Hemiptera: Miridae) and green peach aphid, Myzus persicae (Sulzer)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 27 publications
0
13
0
2
Order By: Relevance
“…Autoinoculation devices are not restricted to inoculating the target prey and can be used to attract and contaminate non-host vectors of entomopathogenic fungi. For example, bees are able to vector pathogens to control both plant and insect pests (Kapongo et al 2008a;Al-mazra'awi et al 2006;Carreck et al 2007). Bumble bees, Bombus impatiens (Cresson), were able to vector B. bassiana to sweet pepper plants in glasshouses where they induced infection in populations of the tarnished plant bug, Lygus lineolaris (Palisot de Beauvois) and the western flower thrip F. occidentalis (Al-mazra'awi et al 2006).…”
Section: Assisted Autodisseminationmentioning
confidence: 99%
“…Autoinoculation devices are not restricted to inoculating the target prey and can be used to attract and contaminate non-host vectors of entomopathogenic fungi. For example, bees are able to vector pathogens to control both plant and insect pests (Kapongo et al 2008a;Al-mazra'awi et al 2006;Carreck et al 2007). Bumble bees, Bombus impatiens (Cresson), were able to vector B. bassiana to sweet pepper plants in glasshouses where they induced infection in populations of the tarnished plant bug, Lygus lineolaris (Palisot de Beauvois) and the western flower thrip F. occidentalis (Al-mazra'awi et al 2006).…”
Section: Assisted Autodisseminationmentioning
confidence: 99%
“…For flour‐based carriers/diluents, Israel and Boland concluded that flours were among the least toxic powders to honeybees 15. Indeed, food‐grade products have been used as carrier/diluent to enhance the acquisition capacity of commercially available formulated microbial control agents 3, 6, 7, 14, 29–31. Although wheat flour was not included in the present flight‐cage experiments, it is believed that the results of the laboratory miniature‐dispenser bioassay together with the use of flours in entomovectoring studies provide evidence for their safe use in combinations with bees.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is likely that such test designs are insufficient or even inappropriate for assessing risks of the powder formulations used in entomovectoring strategies. A good example is provided by contact exposure to a wet treatment of the powder formulation Botanigard containing the entomopathogen Beauveria bassiana GHA, which caused 92% mortality, while there was only 6–12% mortality after contact exposure to the dry powder 11, 13, 14. In addition to lethal effects, it is also necessary to evaluate sublethal effects on vector reproduction and behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…(Kevan et al, 2008;. 이 기술의 장점은 화분매개곤충들의 빈번한 방화활동 을 이용하여 병해충 방제가 필요한 꽃이나 잎에 정확히 미생물 제제를 운반함으로써, 수분활동에 의한 농작물 수량증대 및 품 질향상의 이점과 더불어 병해충의 효과적인 방제를 위해 요구 되는 미생물제제의 잦은 살포라는 단점을 보완할 수 있다 (Sutton and Peng, 1993;Shipp et al, 1994;Kevan et al, 2008; (Peng et al, 1992;Yu and Shutton, 1997 (Al-mazra'awi et al, 2006a(Al-mazra'awi et al, , 2006bKapongo et al, 2008a), 해충 방제제(Beauveria bassiana)와 병 방제제 (Clonostachys rosea)를 혼용하여 분배장치에 투여함으로써 해충과 식물병원균을 동시에 방제하는 기술까지 발전하였다 (Kapongo et al, 2008b). 보다 최근에는 미생물제제의 운반효율을 제고할 수 있는 분배장치개발 (Mommaerts et al, 2010a), 적용 가능한 제제 선발 (Mommaerts et al, 2010b), 비벡터링 기술 적용시 천 적들에 대한 영향 (Shipp et al, 2012)등이 연구되어 기술의 실 용화에 성큼 다가서고 있다.…”
unclassified
“…본 연구 에서는 또한 제제 교체주기와 관련해서 주 1회, 2회로 나누어서 검정하였는데, 모두 유사하게 나타나 큰 차이를 보이지는 않았 다. 그러나, 비벡터링에서는 분배장치내에 공급하는 제제가는 수화제 형태로 분말상태의 제제를 사용하기 때문에 제제가 공 기중에 노출됨으로써 습해지거나 분배장치를 통과하는 뒤영벌 의 배설 등에 의해서 굳어져서 벌 충체에 묻는 양이 적어질 수 있어 시설내 습도가 높은 계절에는 일주일에 2회 정도는 분배 제효과도 우수해야 되지만, 매개자인 벌에 대한 독성 및 부작용이 없거나 낮아야 사용이 가능하다(Kevan et al, 2008; Kapongo et al (2008aKapongo et al ( , 2008b…”
unclassified